Acute toxicity test of standardized ethanolic extract of Senggugu (Clerodendrum serratum L. Moon) root bark - Wahyono .; Lukman Hakim; Nurlaila .; Marlin Sulistio; Rosmulyati Ilyas (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The goal of this research was to assess the potency of acute toxicity, evaluate clinical symptoms, spectrum of toxic effect and mechanism that caused the death of animal test after administration of standardized ethanolic extract of senggugu (Clerodendrum serratum L.Moon) root bark to Balb/C male mice.The research used completely randomized design. The animal test was Balb/C male mice, healthy, age 2-3 months with uniform body weight. Twenty-five mice were grouped into 5 groups, including 1 control group with administration of 0.5 % CMC Na and 4 experimental groups. The dosage for each group were 0.73; 1.21 ; 2.03; and 3.38 g/kg of body weight, respectively. Evaluation of the toxic symptoms and death of animal test was done for 24 hours. If the animal test was died before 24 hours then it underwent surgery to take the heart, liver, lung, kidney, gastric, and intestine. In the end of the evaluation, all mice were killed to take the vital organs for histopathologic examination.The test resulted LD50 of standardized ethanolic extract from senggugu root bark using Balb/C male mice was 1.57 g/kg of body weight. It was categorized as moderately toxic. Administration of the extract caused alterations of animal behaviours including vocalization, passiveness and mucus secretion. Histopathology examination shows infiltration of lymphocyte and neutrophil in intestinal mucous after administration of the extract.Key words: standardized ethanolic extract, Clerodendrum serratum L.Moon, LD50